2021
DOI: 10.1080/21645515.2020.1855954
|View full text |Cite
|
Sign up to set email alerts
|

Association of vaccine awareness and confidence on the influenza vaccination status of Al Ahsa, Saudi Arabia residents

Abstract: While the Saudi Arabian Ministry of Health has made seasonal influenza vaccination available for several years, there remains a scarcity of vaccination coverage reports outside of the capital city. Understanding factors that affect vaccine uptake is important in developing strategies to improve coverage. This analytic cross-sectional study utilized data from 1377 adult residents randomly selected through a multi-stage sampling procedure from the three administrative sectors of Al Ahsa, Saudi Arabia. Estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…14 However, the Saudi Arabian Ministry of Health recommends annual seasonal influenza immunisation for everyone over 50 years old. 8,15 These findings reinforce the notion that the most significant barrier to a lifetime immunisation practice is the lack of knowledge noticed in the elderly. Furthermore, patients underestimate the severity and impact of influenza, making them reluctant to seek a vaccine.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…14 However, the Saudi Arabian Ministry of Health recommends annual seasonal influenza immunisation for everyone over 50 years old. 8,15 These findings reinforce the notion that the most significant barrier to a lifetime immunisation practice is the lack of knowledge noticed in the elderly. Furthermore, patients underestimate the severity and impact of influenza, making them reluctant to seek a vaccine.…”
Section: Discussionsupporting
confidence: 70%
“… 14 However, the Saudi Arabian Ministry of Health recommends annual seasonal influenza immunisation for everyone over 50 years old. 8 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…Sixty-one studies reported perceived barriers to receiving an influenza vaccination in the total population ( Table 4 ) [ 16 , 17 , 19 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , …”
Section: Resultsmentioning
confidence: 99%
“…Barrier types were further assessed to determine the key factors (determined by agreement rate) across the general and unvaccinated population for not receiving an influenza vaccine. The top-five barriers to influenza vaccination, as reported by the total population compared to the unvaccinated population, are illustrated in Figure 3 [ 16 , 17 , 19 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , ...…”
Section: Resultsmentioning
confidence: 99%
“… 22 In 2020, after the outbreak of the new crown epidemic, Chinese citizens’ enthusiasm for influenza vaccination was unprecedentedly high. 26 However, the production cycle of influenza vaccines needs at least 5 months, and the validity period is 1 year. It cannot be used across the year, and there is little room for regulation of temporary increase in production.…”
Section: Discussionmentioning
confidence: 99%